SISTEM PENGHINDAR HALANGAN OTOMATIS PADA TWIN-TILTCOPTER DENGAN METODE DCM DAN PID - , BENEDICTUS BENNY WIJANARKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The goal of this research is to make an automatic obstacle avoidance system for a Twin-tiltcopter that can make it flies without any collisions with objects ahead. The Automatic Obstacle Avoidance System is build based on Arduino Uno. Using an ultrasonic sensor as a distance sensor, the twin-tiltcopter will detect the distance with obstacle ahead on its course. Direct Cosine Matrix is applied for the sensor fusion algorithm. This research also applied PID Algorithm to balance the twin-tiltcopter. The Obstacle Avoidance System will compare the detected distance values with the set point of distance values. The comparison value will be used by the system to drive the servos of the twin-tiltcopter and to avoid any obstacles on its course. The implemented Automatic Obstacle Avoidance System is able to make the twin-tiltcopter to perform obstacle avoidance while itâs flying at the maximum speed of 70.40 cm/s and the maximum distance of 200 cm